IN VITRO STUDY OF SUPERFICIAL ENAMEL LAYER OF PERMANENT TEETH DURING STAGE OF SECONDARY MINERALIZATION - G.M. Grigorenko; L.A. Khomenko; G.V. Sorochenko; L.M. Kapitanchuk (Ukrainian Medical Stomatological Academy, 2015)
Introduction. The lowest level of mineralization of hard dental tissues is observed during the first year after teeth eruption. This is confirmed by significant increase of prevalence and intensity of caries in permanent teeth from 6 to 15 years. Enamel caries-resistance changes during secondary mineralization. These confirm importance of the study of changes in the properties of the superficial enamel layer of permanent teeth during the period of intensive secondary mineralization. The aim of the research - in vitro study of the chemical composition and morphological structure of the superficial enamel layer of permanent teeth immediately after their eruption and 12 months later. Object and methods of the research. We used for the study 15 samples of enamel of permanent teeth (erupted not later than 6 months ago premolars of 11-13 years old children). Initial research group included 5 samples of enamel. The remaining 10 samples were randomly divided into two equal groups (6 months and 12 months) and placed into two boxes that were filled with artificial saliva (T. Fusayama, 1975). The studied samples were not treated with any preventive means. Enamel samples were studied at the beginning of the experiment, 6 and 12 months later. Surface of the samples at the first stage of the research was analyzed by the scanning electron microscope (SEM, INCA PENTA FET×3, Oxford Instruments, Co., UK), at the second stage quantitative chemical composition was determined by X-ray photoelectron spectroscopy (X-ray, EDS) with Auger microprobe JAMP -9500F (Japan). The results were calculated in weight percentage. The research results indicate that during 12 months of the experiment significant changes of the quantity of major chemical elements were not found (p> 0.05). Tendency of increase of calcium, phosphorus, fluorine, nitrogen content, calcium / phosphorus ratio and decrease of carbon, oxygen and sodium content was found. Initial calcium content was 20,47 ± 1,07, 6 months later - 21,12 ± 0,84, 12 months later - 21,62 ± 0,71 (p> 0.05). Amount of phosphorus at the beginning of experiment was 14,83 ± 0,41, 6 months later - 14,98 ± 0,41, 12 months later - 15,12 ± 0,53 (p> 0.05). Amount of carbon in the enamel samples at the beginning of experiment was 8,22 ± 0,73, 6 and 12 months later - 8,06 ± 0,57 and 7,23 ± 0,51 respectively (p> 0.05). Calcium / phosphorus ratio at the beginning of the experiment was 1,38 ± 0,08, 6 months later - 1,41 ± 0,04, 12 months later - 1,43 ± 0,05 (p> 0.05). Electron microphotographs showed changes of the ultrastructure of the enamel surface. On the surface of enamel at the beginning of the experiment perikymata can be seen, on the border of which oulets of arcade-like enamel prisms are seen, enamel surface is din and rough. 12 months later perikymata become smoothed, enamel is matte, rough, there is a significant number of depressions that indicate the outlets of enamel prisms. Conclusions. The research results indicate that tooth enamel of just erupted teeth is not mineralized and respectively has insufficient level of caries-resistance. After 12 months of the experiment visible signs of mineralization of enamel surface were observed, but statistically significant evidence of mineralization during research was not found. The level of enamel caries-resistance remains insufficient even 12-18 months after the teeth eruption. During this period the enamel of permanent teeth is especially susceptible to the action of cariogenic factors of the oral cavity. Therefore, for prevention of destruction of hard dental tissues of permanent teeth during 12-18 months after eruption prescription of mineralizing means is advisable.